The Drabo corymbosae-Papaveretea dahliani − a new vegetation class of the High Arctic polar desert - Daniëls, Fred J.A.; Elvebakk, Arve; Matveyeva, Nadezhda V.; Mucina, Ladislav (Hacquetia, 2016)
A new class and a new order (Drabo corymbosae-Papaveretea dahliani and Saxifrago oppositifoliae-Papaveretalia dahliani) have been described, and the Papaverion dahliani validated. This is vegetation of zonal habitats in lowlands of the High Arctic subzone A (or Arctic herb, cushion forb or polar desert subzone) and of ecologically equivalent sites at high altitudes on the mountain plateaus of the High Arctic. The new class spans three continents – North America (Canadian Arctic Archipelago and Greenland), Europe (parts of Svalbard and Franz Josef Land), and Asia, including northern regions of Chelyuskin Peninsula (Taymir Peninsula), Severnaya Zemlya Archipelago and De Longa Islands.